PENGARUH UKURAN PERUSAHAAN, UMUR PERUSAHAAN DAN KEPEMILIKAN MANAJERIAL TERHADAP KINERJA KEUANGAN PERUSAHAAN - Kusnarti, Alvie; Iswara, Ulfah Setia (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2025)
This research examines and analyzes the effect of firm size, age, and managerial ownership on the financial performance of banking companies listed on the Indonesia Stock Exchange (IDX) during 2020-2023. Company financial performance reflects how the firm manages its finances to maximize its performance. Furthermore, the research applies quantitatively. The data collection technique used was purposive sampling, in which the sample was based on the criteria given. In line with that, there were 72 companies as samples from 18 banking companies listed on IDX from 2020-2023. Moreover, the data analysis technique used multiple linear regression with SPSS (Statistical Product and Service Solutions).The result indicates that firm size has a positive effect on company financial performance. Similarly, firm age has a positive effect on company financial performance. On the other hand, managerial ownership does not affect the company financial performance.